PENGARUH KREDIBILITAS MEREK TERHADAP SENSITIVITAS HARGA KONSUMEN UNTUK KATEGORI PRODUK LAPTOP - Eny Rachmawati (Universitas Tribhuwana Tunggadewi, 2017)
Research actually aims at examination and taking empirical evidence on: (1) Wheter brand credibility impacts on consumer’s price sensitivity; (2) Whether brand credibility has indirect impact on consumer’s price sensitivity through perceived quality and expected utility, (3) Whether brand credibility has indirect impact on consumer’s price sensitivity through perceived risk and expected utility, (4) Whether brand credibility has indirect impact on consumer’s price sensitivity through informasi cost and expected utility. Research populasi is this study of students in Mayjen Sungkono Mojokerto University use and buy brand laptop. The number of responden is 100 students and the sample was taken was using probability sampling. The sampling collection techniques is proportional sampling while research data analysis path. Results of research indicate that: (1) more and more high brand credibility, more and more decrease consumer’s price sensitivity; (2) more and more hight brand credibility, cause perceived quality of product higher increase perception expected utility higher, reduse the consumer’s price sensitivity; (3) more and more hight brand credibility, cause decrease informasi cost higher increase perception expected utility higher, reduse the consumer’s price sensitivity